The Influence of Family Characteristics, Lifestyle, Social Media, and Environmental Support on Generation Z's Interest in Horticultural Farming in South Kalimantan - Muhammad Alif; Yuanita Setyastuti; Astinana Yuliarti; Muhammad Ghalih; Ezio Marra (LPPM Universitas PGRI Sumatera Barat, 2026)
Young people have experienced changes in the era of modern societal development. Most rural residents perceive that agricultural work is no longer attractive, so many young people choose jobs outside the agricultural sector. This study aims to analyze the influence of digital media utilization, environmental support, and family characteristics on Generation Z’s lifestyle and interest in horticultural farming. Data collected include primary and secondary data through interviews using questionnaires. Data was processed and analyzed using scores, Linear Regression, and Partial Least Squares Structural Equation Modeling (PLS-SEM). The structural model analysis using PLS-SEM revealed several significant relationships. The path coefficient for digital media utilization on Generation Z’s lifestyle is 0.083 with a t-statistic of 2.877 (p = 0.004), indicating significance. However, the influence of social media on interest in horticultural farming is not significant (p = 0.328). Environmental support and family characteristics also significantly affect Generation Z’s lifestyle and interest in farming. R-Square (R²) for lifestyle is 0.799, indicating that 79.9% of lifestyle variation is explained by the exogenous variables. For interest in horticultural farming, the R² value is 0.717, meaning 71.7% of the interest variation is influenced by the factors in the model. The Q-Square (Q²) values for both variables are 0.610 and 0.611, indicating the model has good predictive power. These results highlight the significant role of family factors and lifestyle in Generation Z’s interest in horticultural farming.